PENGARUH EXPERIENTIAL MARKETING DAN EMOTIONAL MARKETING TERHADAP LOYALITAS PELANGGAN (Studi pada Klinik Kecantikan Zidya Klinik Pratama) - Wijayanti, Maya Risma; Othman, Lie (Jurnal Daya Saing, 2025)
The increasingly tight competition in the beauty industry encourages clinics to focus on marketing strategies that can build customer loyalty. This study aims to determine the effect of experiential marketing and emotional marketing on customer loyalty at Zidya Klinik Pratama in Pekanbaru City. This study uses a quantitative approach with a survey method by distributing questionnaires to 95 respondents who are active customers. The data analysis technique uses multiple linear regression to test the relationship between variables. The results of the study indicate that experiential marketing has a positive and significant effect on customer loyalty, as does emotional marketing. Simultaneously, both variables also have a significant effect on customer loyalty. This shows that memorable experiences and emotional attachments play an important role in shaping customer loyalty to beauty clinic services. These findings recommend that Zidya Klinik Pratama continue to develop marketing strategies that focus on customer experience and emotional approaches consistently to maintain and increase customer loyalty.